Performance of Oxidation Ponds in Removing Heavy Metals from Pig Farm Wastewater - Ling, Teck Yee; Lipan, Sylvia; Singh, Harwant (IDOSI Publication, 2010)
Pig manure is a source ofheavy metals which may cause pollution if not properly managed. Oxidation pond system is an economical method of wastewater treatment commonly used in pig farms to reduce water pollution. However, the fate of heavy metals in different oxidation pond systems in pig farm are lacking in literature. Therefore, in this study heavy metals in pig feed, fresh manure and wastewater and sediment from pond inflow and outflow of farms with one pond, two ponds, two ponds with separator and three ponds in series were investigated. Results indicate that heavy metals content in manure were in decreasing order of Cu>Zn»>Cr>Pb>Ni>Cd and they were highly correlated with the feed (r=0.90). Reduction ofheavy metals in the wastewater was in decreasing order of Cu( 62 %» Zn(36%» Ni(34 %»Pb«31 % »Cd(16%»Cr(9%) and th e reductions were significantly higher in the 3-pond system than the other systems. Copper and zinc were the highest in concentrations in the pond sediment (833 and 655 mglkg respectively) whereas the other heavy metals ranged from 17 to 81 mglkg. Reductions of heavy metals in the sediment between inlet and outlet sediment of the 3-pond system (47%) was significantly higher than the other three systems «16%). The concentration of Cd in the outflow of all the pond system studied exceeded the 0.02 mgIL Malaysian standard set for the discharge downstream of water intake indicating its mobility and thus the need of other methods to polish the effluent for compliance.